Merengkuh Kesemestaan - Albertus Bagus Laksana (Societas Dei: Jurnal Agama dan Masyarakat, 2023)
The book La grâce du végétal presents unique and fresh theological reasoning regarding the “divine economy”. The world of plants or vegetation is a blessing not only for themselves but also for other creatures, including humans, in relationships. In the ecological crisis, it is increasingly recognized that plants are "providers of life". Plants perceive, feel, and communicate… beyond their seemingly mute appearance. We live with trees in a relationship marked by resonance and dependence. Schaefer offers a concept of "significative reciprocity", namely a reciprocal relationship that is important for both sides because humans also preserve themselves when humans look after trees. If this logic is continued, it might lead to a big conclusion: everything is a blessing for others. Perhaps there was an element of coincidence when I saw the book displayed on an obvious shelf. However, beyond this interest and element of coincidence, perhaps this topic also represents a movement of thinking in the broader field of theology and religious thought, which is not only increasingly inclusive but also "universal", in the sense of embracing the universe. This idea clearly expands the breadth of the inclusive movement of theology and religious thought, which has penetrated geographical and regional boundaries (theology without borders) or denominational boundaries (ecumenical) and religious boundaries (interreligious).